Autonomic and Electrocardiographic Examination in Patients with Chronic and Inactive Lepromatous Leprosy and Compared Peripherie Nerve Conduction Studies - Ulvi, Hızır; Yiğiter, Remzi; Yoldaş, Tahir; Dolu, Yücel; Müngen, Bülent (Fırat University, 2002)
Aim: The aim of this study was to investigate and compare the autonomic and electrocardiographical examination in patients with chronic and inactive lepromatous leprosy with peripheric nerve conduction studies. Material and Method: In our study, we included 37 lepromatous leprosy patients (mean age: 38±17 years;17 males and 20 females) and 59 normal subjects (mean age: 49±13; 24 males and 35 females) as control group. 12 leads ECG were recorded at a speed of 50 mm/s and nerve conduction parameters were studied in all the subject. QT and JT intervals were measured. Results: Using Bazett formula, these inlevals were corrected for heart rate. Mean QT interval, JT interval. QTc interval, JTc interval, RR interval, QT dispersion (d), JT-d, QTc-d and JTc-d (344±37 ms, 283±34 ms. 12±0.61 ms, 10±0.82 ms, 760±140 ms, 80±33 ms, 66±29 ms, 3±1.4 ms and 2.5±1.3 ms; respectively) in lepromatous leprosy patients were significantly longer than that of the normal subjects (372±27 ms, 296±29 ms. 13±0.83 ms, 10±0.73 ms, 811 ± 125 ms, 30±11 ms. 28±12 ms, 1±0.37 ms and 0.97±0.36 ms; respectively) (p

Amaç: Bu çalışmanın amacı kronik ve aktif olmayan lepramatöz lepralı hastalarda otonomik ve elektrokardiyografik incelemenin periferik sinir ileti çalışmaları ile karşılaştırılmasıdır. Gereç ve Yöntem: Çalışmamıza yaş ortalaması 38±17 olan 17'si erkek. 20'si kadın toplam 37 lepralı olgu ile yaş ortalaması 49±13 olan 24'ü erkek. 35'i kadın toplam 59 sağlıklı gönüllü alındı. Her iki gruptaki her olguda 50 mm/sn hızında 2 mV amplitüdünde standart 12 derivasyon elektrokardiyografi (EKG) çekimleri ve periferik sinirlerde standart ileti çalışması yapıldı. QT ve JT intervali ölçüldü. Bulgular: Bazet formülünden hıza göre düzeltilmiş QT (QTc) ve JT (JTc) intervalleri hesaplandı. Lepramatöz lepralı hastaların ortalama QT. JT, QTc, JTc, RR intervalı, QT. JT, QTc, JTc dispersiyon (d) değerleri (sırasıyla: 344±37 ms, 283±34 ms, 12±0.61 ms, 10±0.82 ıns. 760±140 ms, 80±33 ms. 66±29 ms, 3±1.4 ms ve 2.5±1.3 ms) kontrol grubundan (benzer olarak sırasıyla 372±27 ms, 296±29 ms, 13±0.83 ms, 10±0.73 ms, 811±125 ms, 30±11 ms, 28±12 ms, 1±0.37 ms ve 0.97±0.36 ms) anlamlı derecede uzamıştı (p
KRONİK VE AKTİF OLMAYAN LEPRAMATÖZ LEPRALI HASTALARDA OTONOMİK VE ELEKTROKARDİYOGRAFİK İNCELEMENİN PERİFERİK SİNİR İLETİ ÇALIŞMALARI İLE KARŞILAŞTIRILMASI